INFLUENCE OF POLICIES, WORKER FACTORS, ENVIRONMENT, AND SUPERVISION ON OSH IMPLEMENTATION AT BALONGAN REFINERY UNIT VI - Firmansyah, Dicky; Sukwika, Tatan; Erislan, Erislan (International Journal of Health Science & Medical Research, 2025)
The International Labour Organization (ILO) reports more than 2.78 million deaths annually due to work-related accidents and diseases, along with approximately 374 million non-fatal accidents. The novelty of this research lies in testing a comprehensive model that integrates four organizational and human factors with safety culture as a mediator, which is rarely applied in Indonesia’s oil and gas industry. This study investigates the effects of OHS policy commitment, worker factors, work environment, and supervision on OHS implementation, with safety culture as a mediating variable, at Balongan Refinery Unit (RU) VI. Using an explanatory quantitative approach, 165 employees were surveyed and analyzed with SEM-PLS. Findings reveal that worker factors significantly influence both OHS implementation and safety culture, while policy commitment and supervision affect safety culture but not implementation. The work environment has no significant role, and safety culture was not confirmed as a mediator. Worker compliance emerged as the strongest determinant, whereas OHS knowledge was the weakest aspect. Though focused on RU VI, the results offer broader insights for other refinery units with similar high-risk operations.